Paper Circuit Project-based STEAM Learning to Enhance Student Understanding and Creativity - Arnie Novianti Zulkarnain; Eka Cahya Prima; Nanang Winarno; Bevo Wahono (Journal of Science Learning, 2024)
Students believed physics was one of the most challenging sciences in education, and their interest in learning physics was lacking. Therefore, this study aims to enhance students' understanding and creativity in the STEAM learning system on electricity by creating a project (Paper Circuit) using the students' creativity at the junior high school level—quantitative research with a pre-experimental design used for this study. The population is 8th grade and 9th grade (50 students adapted to the curriculum used in the school) in one of the Junior Secondary Schools located in Bandung and Cimahi, Indonesia. The data is obtained from the pretest-posttest results, which show that the average pre-test score was 57.04 and the post-test score was 76.64. The nonparametric test was tested using the Wilcoxon test to measure student understanding. The results from e Wilcoxon are .000, which shows sig. 0.05, which means there is a significant difference between pre-test and post-test. Students' creativity is obtained from the Creativity Product Analysis Matrix (CPAM), and the result for Project 1 is 73.71%, categorized as enough, and Project 2 is 83.13%, categorized as good. Based on the result, Paper Circuit STEAM project-based learning can enhance student understanding and creativity. STEAM project-based learning can be used as an alternative teaching strategy in junior secondary school.